Unusually high birch (Betula spp.) pollen concentrations in Poland in 2016 related to long-range transport (LRT) and the regional pollen occurrence - Myszkowska Dorota; Piotrowicz Katarzyna; Ziemianin Monika; Bastl Maximilian; Berger Uwe; Dahl Åslög; Dąbrowska-Zapart Katarzyna; Górecki Artur; Lafférsová Janka; Majkowska-Wojciechowska Barbara; Malkiewicz Małgorzata; Nowak Małgorzata; et al. (SPRINGER, 2025)
In 2016, the highest birch (Betula spp.) pollen concentrations were recorded in Krakow (Poland) since the beginning of pollen observations in 1991. The aim of this study was to ascertain the reason for this phenomenon, taking the local sources of pollen in Poland and long-range transport (LRT) episodes associated with the pollen influx from other European countries into account. Three periods of higher pollen concentrations in Krakow in 2016 were investigated with the use of pollen data, phenological data, meteorological data and the HYSPLIT numerical model to calculate trajectories up to 4 days back (96 h) at the selected Polish sites. From 5 to 8 April, the birch pollen concentrations increased in Krakow up to 4000 Pollen/m(3), although no full flowering of birch trees in the city was observed. The synoptic situation with air masses advection from the South as well as backward trajectories and the general birch pollen occurrence in Europe confirm that pollen was transported mainly from Serbia, Hungary, Austria, the Czech Republic, Slovakia, into Poland. The second analyzed period (13-14 April) was related largely to the local flowering of birches, while the third one in May (6-7 May) mostly resulted from the birch pollen transport from Fennoscandia and the Baltic countries. Unusual high pollen concentrations at the beginning of the pollen season can augment the symptomatic burden of birch pollen allergy sufferers and should be considered during therapy. Such incidents also affect the estimation of pollen seasons timing and severity.